Clive Barker dark imaginer - Ní Fhlainn, Sorcha, 1980-; Frost, Matthew; Manchester University Press (Manchester, UK : Manchester University Press, 2017)
" 'Clive Barker: Dark imaginer' explores the diverse literary, film and visionary creations by the influential British artist Clive Barker. Met with critical acclaim in the mid-1980s for his unique contribution to the horror genre with Books of Blood (1984-85), Barker has remained curiously overlooked in scholarly circles for decades, despite his continued success as a bestselling author, filmmaker and producer, and sought-after visual artist. In this necessary and timely scholarly collection, these innovative essays by leading scholars in the fields of literature, film and popular culture, explore Barker's contribution to gothic, fantasy, and horror studies, and interrogate his creative legacy. The volume consists of an extensive introduction and twelve ground-breaking essays that critically reevaluate Barker's oeuvre. These scholarly examinations range from critical discourses on splatterpunk and body horror, the Thatcher era, and the dark fantastique, to queer(ing) desire, anti-horror, iconic monsters and demons, and the influence of the gothic mode. There are also in-depth analyses of both his celebrated and lesser known novels, his short stories, theme park designs, screen and comic book adaptations, film direction and production, sketches and book illustrations. 'Clive Barker: Dark imaginer', which also includes various illustrations by Barker himself, reveals the breadth and depth of his distinctive dark vision, which continues to fascinate and flourish. The book is for fans of Clive Barker, and scholars and students interested in its many disciplines. It is an essential study of an extraordinary polymath" --Back cover.
Clive Barker: Dark imaginer explores the diverse literary, film and visionary creations of the polymathic and influential British artist Clive Barker. In this necessary and timely collection, innovative essays by leading scholars in the fields of literature, film and popular culture explore Barker's contribution to gothic, fantasy and horror studies, interrogating his creative legacy. The volume consists of an extensive introduction and twelve groundbreaking essays that critically reevaluate Barker's oeuvre. These include in-depth analyses of his celebrated and lesser known novels, short stories, theme park designs, screen and comic book adaptations, film direction and production, sketches and book illustrations, as well as responses to his material from critics and fan communities. Clive Barker: Dark imaginer reveals the breadth and depth of Barker's distinctive dark vision, which continues to fascinate and flourish.
Introduction: 'To darken the day and brighten the night': Clive Barker, dark imaginer -- Sorcha Ní FhlainnPart I: Origins1 'Visions of another Albion': the Books of Blood and the horror of 1980s Britain -- Darryl Jones -- 2 'Marks of weakness, marks of woe': the Books of Blood and the transformation of the weird -- Kevin Corstorphine -- 3 When fantasy becomes reality: social commentary of 1980s Britain in Clive Barker's Weaveworld - Edward Timothy WallingtonPart II: Screening Barker4 The joyless magic of Lord of Illusions -- Harvey O'Brien -- 5 Drawing (to) fear and horror: into the frame of Clive Barker's The Midnight Meat Train and Dread comic and film adaptations -- Bernard Perron -- 6 Beauty, pain and desire: gothic aesthetics and feminine identification in the filmic adaptations of Clive Barker -- Brigid CherryPart III: Labyrinths of desire7 Clive Barker's queer monsters: exploring transgression, sexuality and the other -- Mark Richard Adams -- 8 Breaking through the canvas: towards a definition of (meta)cultural blackness in the fantasies of Clive Barker -- Tony M. Vinci -- 9 'A far more physical experience than the cinema affords': Clive Barker's Halloween Horror Nights and brand authorship -- Gareth JamesPart IV: Legacy10 'What price wonderland?': Clive Barker and the spectre of realism -- Daragh Downes -- 11 Clive Barker's late (anti-)horror fiction: Tortured Souls and Mister B. Gone's new myths of the flesh -- Xavier Aldana Reyes -- 12 The Devil and Clive Barker: Faustian bargains and gothic filigree -- Sorcha Ní Fhlainn -- Index.
In-house editor: Matthew Frost.
Includes bibliographical references and index.
Students and lecturers in twentieth-century and contemporary Gothic and horror studies.
In English.
Description based on print record.
Available through ManchesterHive.
Keywords: Barker, Clive, -- 1952-; Barker, Clive, -- 1952- -- Criticism and interpretation; Barker, Clive, -- 1952-; Gothic fiction (Literary genre), English -- History and criticism; LITERARY CRITICISM / Gothic & Romance; Gothic fiction (Literary genre), English; Criticism, interpretation, etc